The agony of Greek Jews, 1940 - 1945 - Bowman, Steven B. 1942- (Stanford Univ. Press, 2009)
The Jews of Greece to World War I -- Germans and Jews in Greece -- In victory and defeat -- Vernichtungsorganisierung -- Chronicle of the deportations -- Abnormal deaths in a foreign land -- How a remnant survived -- Freedom or death -- Relief and rescue -- Bitter homecoming